2000
DOI: 10.1038/35023579
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegenerative stimuli induce persistent ADF/cofilin–actin rods that disrupt distal neurite function

Abstract: Inclusions containing actin-depolymerizing factor (ADF) and cofilin, abundant proteins in adult human brain, are prominent in hippocampal and cortical neurites of the post-mortem brains of Alzheimer's patients, especially in neurites contacting amyloid deposits. The origin and role of these inclusions in neurodegeneration are, however, unknown. Here we show that mediators of neurodegeneration induce the rapid formation of transient or persistent rod-like inclusions containing ADF/cofilin and actin in axons and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
451
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 351 publications
(485 citation statements)
references
References 48 publications
33
451
0
1
Order By: Relevance
“…It was previously reported that cofilin-actin rods were not labeled with phalloidin, an agent which specifically labels F-actin (11,13). Consistently, fluorescence from Texas red phalloidin did not colocalize with cofilin-GFP (Fig.…”
Section: The Rod-like Structure Induced By Cofilin Overexpression Consupporting
confidence: 56%
See 3 more Smart Citations
“…It was previously reported that cofilin-actin rods were not labeled with phalloidin, an agent which specifically labels F-actin (11,13). Consistently, fluorescence from Texas red phalloidin did not colocalize with cofilin-GFP (Fig.…”
Section: The Rod-like Structure Induced By Cofilin Overexpression Consupporting
confidence: 56%
“…ADF͞cofilin-actin rods are also found in cultured rat hippocampal neurons treated with neurodegenerative stimuli (11). In this case, the neurodegenerative stimuli (e.g., glutamate treatment) appear to induce ADF͞cofilin overactivation and lead to the formation of ADF͞cofilin rods.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…On the basis of the critical role of actin in the formation of new synapses and the maintenance of synaptic integrity, we hypothesize that overproduction of beta-amyloid (Ab) peptide, by inhibiting dynamic changes in actin polymerization, would lead to neurite retraction and synaptic dysfunction. Neurodegenerative stimuli can induce the formation of actin rods 5 where Ab has been shown to accumulate, and which block transport within neurites 6 . Retracted neurites and disorganized actin filaments are major components of senile plaques and neurofibrillary tangles (NFTs) 7 , which are hallmarks of AD.…”
mentioning
confidence: 99%